The Polarization of Ice (O Polyarizatsii Lda) - Averbukh,R. E.; Kosman,M. S. (1950)
The polarization of ice was subjected to study by means of a new arrangement of the ballistic method. It was established that the dielectric permeability of ice consists of two parts, sharply differentiated in magnitude, in accordance with the charging interval and the direction of the field. (Author) Trans. of Zhurnal Eksperimentalnoi i Teoreticheskoi Fiziki (USSR) v19 n11 p971-972 1949, by William Mandel.